Praktikat mjekësore popullore si burim i sigurimit të jetës në fshatrat Arnaute të detit Azov në fillim të shekulit XXI - Novik, Alexander A (Seminari Ndërkombëtar për Gjuhën, Letërsinë dhe Kulturën Shqiptare, 2019)
The study is devoted to the description different domiciliary healing practices with improvised means and the analysis of cases when medical treatment is sought from sorceresses that work in the Arnaut community in South Russia; the ethnographic material is compared with the traditions of Albanian and Bulgarian folk medicine. The research includes a wide scope of data collected by means of participant observation, several interviews with sorceresses, and texts of verbal spells. Maintenance of self-treatment practices and popularity of wise women are analyzed through the conception of limited resources, in the case of Arnauts in South Russia the village community lacks professional medical care, technical equipment of medical stations, mobility and money. Field work studies in Rostov on Don region are organized by Peter the Great Museum of Anthropology and Ethnography (Kunstkamera) of the Russian Academy of Sciences and St. Petersburg State University in 2015–2018. The data are collected in villages Margaritovo, Chumbur-Kosa etc. The digital and material archive of the expeditions is registrated at the Kunstkamera, St. Petersburg.